2020
DOI: 10.1186/s13567-020-00854-1
|View full text |Cite
|
Sign up to set email alerts
|

Zinc uptake system ZnuACB is essential for maintaining pathogenic phenotype of F4ac+ enterotoxigenic E. coli (ETEC) under a zinc restricted environment

Abstract: Zinc is the second trace element of living organisms after iron. Given its crucial importance, mammalian hosts restrict the bioavailability of Zinc ions (Zn2+) to bacterial pathogens. As a countermeasure, pathogens utilize high affinity Zn2+ transporters, such as ZnuACB to compete with the host for zinc. It is essential for bacteria to maintain zinc homeostasis and thus maintain their physiology and pathogenesis. In an attempt to uncover the zinc transporter in F4+ enterotoxigenic E. coli (ETEC) C83902, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…STm overcomes calprotectin-mediated zinc chelation by expressing a high-affinity zinc transporter protein (ZnuACB), allowing STm to proliferate normally in the face of intestinal inflammation and to outcompete commensal bacteria [134]. Most bacteria, such as E. coli, Salmonella, and Brucella, take up zinc and counteract zinc deficiency through the ZnuACB uptake system [135]. Meanwhile, STm utilizes the same strategy to evade the isolation of manganese by calmodulin.…”
Section: Nutritional Immunity: the Struggle For Micronutrients At The...mentioning
confidence: 99%
“…STm overcomes calprotectin-mediated zinc chelation by expressing a high-affinity zinc transporter protein (ZnuACB), allowing STm to proliferate normally in the face of intestinal inflammation and to outcompete commensal bacteria [134]. Most bacteria, such as E. coli, Salmonella, and Brucella, take up zinc and counteract zinc deficiency through the ZnuACB uptake system [135]. Meanwhile, STm utilizes the same strategy to evade the isolation of manganese by calmodulin.…”
Section: Nutritional Immunity: the Struggle For Micronutrients At The...mentioning
confidence: 99%
“…After the znuACB gene was deleted, the virulence of Salmonella Typhimurium (STm) was weakened, but the existence of a ZnuACB transport system allowed the bacteria to resist calprotectin-mediated Zn 2+ chelation and benefit from competition with host microflora [8,27]. Our study also found that the ZnuACB system of enterotoxigenic E. coli (ETEC) F4ac plays an important role in maintaining the formation of biofilms and adherence to porcine small intestinal epithelial cells in vitro under zinc deficiency [31]. Although deletion of the zur gene does not affect the virulence of Staphylococcus aureus (S. aureus) and Mycobacterium tuberculosis (M. tuberculosis), it decreases the mortality of mice infected with STm [32][33][34].…”
Section: Zinc Homeostasis In Bacteriamentioning
confidence: 65%
“…The ZupT group comprises 4 proteins possessing 6–7 TMHs. They facilitate zinc uptake to regulate intracellular and extracellular zinc ion concentrations, contributing to zinc balance [62] , [63] . Within the ZupT group, CD630_10870 and CD630_34830 are canonical ZupT transporters [55] .…”
Section: Resultsmentioning
confidence: 99%